INCIDENCE OF POSTEXTRACTIONAL DENTAL HEMORRHAGES AND ETIOLOGICAL FACTORS TRIGGERING THEIR OCCURRENCE - Oleg Zanoaga; Valentin Topalo; Dumitru Sirbu (Romanian Society of Oral Rehabilitation, 2011)
The study comprised 88 patients who were admitted to the Emergency Hospital within 2007-2009 with complaints of hemorrhage in the oral cavity. Of the total group of patients (88), 73 (82,9±4,4%) had postextractional dental hemorrhages. Analysis of the structure of pathologies which caused occurrence of postextractional dental hemorrhages, has revealed a significant prevalence of general etiological factors (79,5±4,7%) compared with the local ones (20,5±4,7%) (p<0,001).